A re‐evaluation of scaling and root planing - Cobb, Charles M.; Sottosanti, John S. (Journal of periodontology (1970), 2021)
Background Extensive reviews on the role of scaling and root planing (SRP) in the treatment of periodontitis have been previously published. This commentary will address the importance of subgingival calculus in the progression and treatment of periodontitis and addresses factors that make the execution of a “definitive” SRP a critical part of therapy. Methods A search for articles, using keywords relevant to the subject , (e.g., periodontitis, dental scaling, root planing, dental calculus, biofilm, inflammation) was conducted using PubMed, Ovid Medline, Cochrane Reviews and the ADA Center for Evidence Based Dentistry data bases. Additionally, references cited in relevant articles were also considered. Results Surfaces of subgingival calculus are covered with a biofilm of metabolically active bacteria. Periodontal inflammation is clearly related to the presence of calculus and biofilm. The primary goal of SRP is removal of subgingival calculus and biofilm deposits to create a biologically compatible root surface and reduce the inflammatory burden. Current evidence suggests that inflammation associated with periodontal infections affects both the immediate oral environment and the patient's systemic health. Conclusion SRP is still critical to the treatment of periodontitis. SRP involving deep probing depths (≥ 5 mm) and root surfaces with anatomical and surface irregularities, regardless of the type of instrumentation, requires time, exceptional skill and perseverance, and patient compliance with periodontal maintenance. Sites with persistent nonresponding probing depths and signs of inflammation following a definitive SRP, should be considered for surgical intervention.